Social Media Utilisation in Institutional Communication: A Conceptual Analysis - Gbaden, Chiakaan Jacob; Robert, Happiness Dah (Darul Yasin Al Sys, 2025)
Social media has fundamentally transformed institutional communication, reshaping how organisations construct meaning, engage stakeholders, and sustain legitimacy. This conceptual paper examines the utilisation of social media in institutional communication, with particular emphasis on tertiary institutions, by drawing on the Uses and Gratifications Theory (UGT) and the Diffusion of Innovations Theory (DOI) to integrate audience-centred and innovation-centred perspectives on institutional adoption and user engagement. The analysis argues that social media has disrupted traditional, top-down communication models and enabled participatory, dialogic interactions that foreground transparency, immediacy, and co-creation. It identifies critical conceptual shifts from managerial to relational communication, from episodic to continuous engagement, and from closed to permeable communicative environments, while highlighting the ethical, strategic, and governance implications of these transformations. Particular attention is given to developing contexts such as Nigeria, where uneven institutional digital capacities and regulatory frameworks shape the dynamics of social media use in tertiary institutions. The paper contends that social media now constitutes a core dimension of institutional identity and legitimacy, thereby demanding new theoretical, methodological, and professional orientations. It concludes by outlining future research directions, including comparative studies, digital legitimacy assessments, and critical examinations of artificial intelligence in institutional communication, thereby advancing a holistic framework for understanding social media’s evolving role in institutional discourse and underscoring the need for adaptive communication theories and practices in a networked public sphere.